(3QSGdI GdMQhas - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3aEf eYfi fYe GdKHGJ hGdOhGe hGdceGd hGdhKGbI ai GdhLhO s
(3BNQgG (B:s
(3CeG GdSDGd GdNWjQ af VQhH SDGdGJg Cf jchf jCMO GdeJbGHdjf abW s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(3999) s
Keywords: (3GdadSaI hGdefWbs